Oksana Laver: GRAMMATICAL EXPRESSION OF EPITHETS IN THE WORKS OF PETRO SKUNTS - Laver, Oksana (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. Well-known Ukrainian writer, the laureate of Taras Shevchenko National Prize Petro Mykolayovych Skunts left a unique poetic legacy, which became a special chapter in the chronicle of civic poetry of Ukraine in the XX – early XXI century. Linguists confirm the richness of the writer’s artistic language, his active use of traditional and innovative techniques in the creation of stylists. The grammatical expression of epithets in the poetic language of the writer has not yet been the subject of linguistic studies, which determines the relevance of our topic. Purpose. The aim of the research is to carry out the linguistic analysis of epithets in the poetic works of P. Skunets and to establish the relationship between the form and content of artistic meanings in accordance with the ideological load of the work. Methods. The scientific work is based on the poetry of P. Skunets from the first two books of the multi-volume edition “Works”, which allows us to trace the evolution of the structure and content of language units with attributive semantics. The main methods in the scientific article were: problem analysis of linguistic and literary works to determine the theoretical foundations of the study; structural, descriptive methods of studying language units, which allows to identify grammatical and semantic features of epithet phrases. Results of the study. Each classification of artistic meanings is based primarily on a broad or narrow understanding of the term ‘epithet’, but the boundary between these two epithets-meanings is quite conditional, in the literary text such a boundary simply disappears. In our work, we used the term epithet in a broad sense to explore not only those linguistic units that are the core of the system of epithets and epithet phrases, but also those that form the periphery of this system. This approach helps to track the main ways of forming epithets within the individual style of the writer. The main function of the epithet is to accurately, concisely, comprehensively and figuratively describe the artistic image, to define, name or create a sign. The function of artistic attribute in P. Skunts’ linguistics is provided by the following lexical and grammatical classes: non-derivative and derivative qualitative adjectives, metaphorized relative and possessive adjectives, verbs, adverbs, adjectives, nouns, We believe that the function of an epithet can be performed by a noun in indirect cases, which give a figurative description of a character or other object. Nouns in the form of the genitive case remain debatable: this form of the substantive genitive is syncretic, because it can simultaneously perform both the function of epithet and the function of metaphor. The formation of an epithet takes place not only on the semantic level, but also on the grammatical path of syntactic, morphological and semantic transposition. Originality. The scientific novelty of the research results is that the linguistic analysis of the grammatical expression of epithets in the works of P. Skunets is carried out for the first time. Conclusion. The results suggest that the study of epithets should not be limited to epithets and adjectives. Successfully selected grammatical form improves the content of the artistic word, deep, multifaceted, sensual, as evidenced by the works of P. Skunts.